2002
DOI: 10.1111/j.1572-0241.2002.05915.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in children 5 years of age and younger

Abstract: Failure to thrive, at the time of presentation, is indicative of a final diagnosis of CD or IC, not UC. Linear growth failure is a common finding in patients with early onset CD. A high proportion of patients with CD have failure to thrive, colonic, and perianal disease. The IBD serology panel is of limited clinical relevance in providing definitive diagnostic information in this pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
82
4
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(106 citation statements)
references
References 35 publications
16
82
4
4
Order By: Relevance
“…We have shown that involvement of the ileum is age dependent: children Ͻ8 years old at the time of diagnosis had significantly less involvement of the ileum and more isolated colonic disease than children Ͼ8 years at diagnosis, confirming previous studies. 7,8,25 In a large study of nearly 1400 North American early-onset patients, Heyman et al 7 demonstrated by multifactorial analysis that a colonic predominant phenotype exists in IBD diagnosed under the age of 8 years. Paul et al 8 studied 413 pediatric IBD patients and also demonstrated a greater tendency for very young patients to present with colonic disease.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that involvement of the ileum is age dependent: children Ͻ8 years old at the time of diagnosis had significantly less involvement of the ileum and more isolated colonic disease than children Ͼ8 years at diagnosis, confirming previous studies. 7,8,25 In a large study of nearly 1400 North American early-onset patients, Heyman et al 7 demonstrated by multifactorial analysis that a colonic predominant phenotype exists in IBD diagnosed under the age of 8 years. Paul et al 8 studied 413 pediatric IBD patients and also demonstrated a greater tendency for very young patients to present with colonic disease.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can affect both children and adults. Early presentation of the disease in the first decades of life carries significant morbidity and mortality (5)(6)(7). A high risk for complications associated with early onset of the disease is thought to reflect longer lifetime duration of disease and medication use, effects of the disease during periods of growth and development, and possibly a more severe phenotype of the disease as a result of a specific genotype-causing predisposition to early onset of the disease.…”
mentioning
confidence: 99%
“…Laboratuvar olarak lökositoz, sola kayma, anemi, trombositoz ve hipoproteinemi, hipoalbüminemi görülebilir. Toksik megakolon akut fulminan kolitin en ciddi formudur (32,39,40,41,42).…”
Section: üLseratif Kolit (üK)unclassified